2014
DOI: 10.3390/molecules191015918
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Synthesis and Cytoselective Toxicity of Monoterpene-Fused 2-Imino-1,3-thiazines

Abstract: Abstract:Starting from pinane-, apopinane-and carane-based 1,3-amino alcohols obtained from monoterpene-based β-amino acids, a library of monoterpene-fused 2-imino-1,3-thiazines as main products and 2-thioxo-1,3-oxazines as side-products were prepared via two-or three-step syntheses. When thiourea adducts prepared from 1,3-amino alcohols and aryl isothiocyanates were reacted with CDI under mild conditions, O-imidazolylcarbonyl intermediates were isolated which could be transformed to the desired 1,3-thiazines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 40 publications
(50 reference statements)
0
20
0
Order By: Relevance
“…The intermediate thiourea adducts 15-17 were prepared in good to excellent yields [33] by the reaction of the appropriate aryl isothiocyanates or ethyl isothiocyanate and 1,3-aminoalcohols 9-11. Methyl iodide treatment of thioureas 15-17 gave thioether intermediates.…”
Section: Synthesis Of 2-imino-13-oxazine Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…The intermediate thiourea adducts 15-17 were prepared in good to excellent yields [33] by the reaction of the appropriate aryl isothiocyanates or ethyl isothiocyanate and 1,3-aminoalcohols 9-11. Methyl iodide treatment of thioureas 15-17 gave thioether intermediates.…”
Section: Synthesis Of 2-imino-13-oxazine Derivativesmentioning
confidence: 99%
“…Compounds 3-8 and thioureas 15a, 15c-e, 16a, 23 and 27-29 were prepared according to literature methods [15,16,28,33,37,38]; all spectroscopic data and physical properties were similar to those reported previously.…”
Section: Introductionmentioning
confidence: 99%
“…1,3-Thiazine derivatives are class of compounds with potential biological activity, such as growth promoting activities [1], anti-fungal activity [2], antiproliferative [3], anti-tumor activity [4], anticancer [5], analgesic activity [6,7], calming activity [8], anticonvulsant activity [9], antibiotic alctivity [10,11], anti-inflammatory [11,12], antimicrobial [13], antimycobacterial [14], antibacterial [15] and antihypertesive [7,16]. On the other hand, pyrimidine derivatives are known to be biologically active compounds and have shown wide range of biological activities like antitubercular [17], antimicrobial, antioxidant and anti-inflammatory [18][19][20], anticancer [21], analgesic, anti-fungal activity, anti-leishmanial, antiviral activity [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the 1,3‐thiazines have been given considerable interest in pharmaceutical research as anti‐inflammatory , antitumor , antibacterial , and antiviral agents . However, only a few studies exploring their anticancer potential have been reported . Moreover, in recent years, attention has been increasingly paid to the synthesis of bis ‐heterocyclic compounds, which exhibit various biological activities .…”
Section: Introductionmentioning
confidence: 99%